2010
DOI: 10.1515/zna-2010-0501
|View full text |Cite
|
Sign up to set email alerts
|

Resonances of a Nonlinear Single-Degree-of-Freedom System with Time Delay in Linear Feedback Control

Abstract: The primary and subharmonic resonances of a nonlinear single-degree-of-freedom system under feedback control with a time delay are studied by means of an asymptotic perturbation technique. Both external (forcing) and parametric excitations are included. By means of the averaging method and multiple scales method, two slow-flow equations for the amplitude and phase of the primary and subharmonic resonances and all other parameters are obtained. The steady state (fixed points) corresponding to a periodic motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…They found that a suitable choice of the feedback gains and time-delays can enlarge the critical force amplitude, and reduce the peak amplitude of the response (or peak amplitude of the free oscillation term) in the case of primary resonance or in the case of super harmonic resonance. El-Bassiouny and El-Kholy [11] discussed the resonances of a nonlinear single-degree-of-freedom system with time delay in linear feedback control. They observed from the frequency-response curves of primary resonance that the response amplitude loses stability to increase time delay.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a suitable choice of the feedback gains and time-delays can enlarge the critical force amplitude, and reduce the peak amplitude of the response (or peak amplitude of the free oscillation term) in the case of primary resonance or in the case of super harmonic resonance. El-Bassiouny and El-Kholy [11] discussed the resonances of a nonlinear single-degree-of-freedom system with time delay in linear feedback control. They observed from the frequency-response curves of primary resonance that the response amplitude loses stability to increase time delay.…”
Section: Introductionmentioning
confidence: 99%